SELF EFFICACY PASIEN HIPERTENSIDI UNIT HEMODIALISA MELALUI EDUKASI PENGENDALIAN TEKANAN DARAH - Edriyani Yonlafado Simanjuntak; Cholina Trisa Siregar (Jurnal Ilmiah Keperawatan, 2019)
Hypertension is a silent killer disease which commonly found but not to give symptoms as a trigger for non-communicable disease, when it occurs continuously and uncontrolled it willcause death. Increase blood pressure requires control and important to anticipate the heart's workload. Uncontrolled blood pressure is associated with poor self-care behavior. Changes behavior in patient are needed based on an understanding of knowledge and self efficacy independently or assisted by the family. Achieving changes behavior in patients is requireself efficacy and as a follow-upeducation is important regarding blood pressure control. The purpose of this study was to determine the effect of blood pressure control education on self efficacy in hypertensive patients in the hemodialysis unit.This type of research is quasi-experimental with nonequivalent design pre-post test with control group. Sampling uses a purposive sampling technique with 64 respondents consisting of 32 respondents in the intervention group and 32 respondents in the control group. Data were analyzed using the Wilcoxon Sign Rank test and Mann Whitney test. The results obtained by the average self-efficacy of patients in the intervention group in controlling blood pressure before education mean 42,19 (SD 2,23) and after education the mean value was 46,03 (SD 1,82). The average self efficacy of the control group patients in controlling blood pressure before education was a mean of 41.03 (SD 41.03) and after education the mean value was 43.69 (SD 3.17). There is an effect of self efficacy in controlling blood pressure before and after education in the intervention group (p = 0.00) and controls (p = 0.00). There is an effect of self efficacy in controlling blood pressure after education between the intervention and control groups (p = 0.00). In conclusion, there is an effect of self efficacy in controlling blood pressure in hypertensive patients in the hemodialysis unit. It is recommended for patients and hospitals or health workers to motivate self efficacy in improving their quality of life.